2004
DOI: 10.1007/s00787-004-0401-3
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, multicenter, open-label assessment of atomoxetine in non-North American children and adolescents with ADHD

Abstract: These open-label data, gathered in an international setting, add to our knowledge of the value of atomoxetine in treating ADHD symptoms, as well as its safety and tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 23 publications
4
32
0
Order By: Relevance
“…Although the duration of atomoxetine treatment in this first study was set at 8 weeks, our findings were comparable to results from similar studies worldwide (Michelson et al 2001;Spencer et al 2001;Biederman et al 2002;Michelson et al 2002;Spencer et al 2002;Buitelaar et al 2004;Kelsey et al 2004), atomoxetine was found to be safe and well tolerated up to 1.8 mg=kg per day.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the duration of atomoxetine treatment in this first study was set at 8 weeks, our findings were comparable to results from similar studies worldwide (Michelson et al 2001;Spencer et al 2001;Biederman et al 2002;Michelson et al 2002;Spencer et al 2002;Buitelaar et al 2004;Kelsey et al 2004), atomoxetine was found to be safe and well tolerated up to 1.8 mg=kg per day.…”
Section: Discussionsupporting
confidence: 90%
“…Information from teachers has extended these findings to the school setting and has shown similar outcomes for both efficacy and safety (Weiss et al 2005). Also, in most trials, the rates of discontinuation due to adverse events were less than 5% (Michelson et al 2001;Spencer et al 2001;Biederman et al 2002;Michelson et al 2002;Spencer et al 2002;Buitelaar et al 2004;Kelsey et al 2004), indicating that atomoxetine is safe and well tolerated in children and adolescents with ADHD. Prior to this study, no placebo-controlled studies had been conducted in Japanese patients.…”
Section: Introductionmentioning
confidence: 80%
“…Improvement in physical functioning was not reported in the other studies of the effects of amphetamine 10,11 or a non-stimulant on HRQOL. [11][12][13][14][15] Improvement to physical motor functioning in our populations was to be expected, considering the demonstrated effects of MPH on fine motor functioning needed for autonomic and creative functions, and handwriting in children with ADHD/DCD. 16,17 Unfortunately, the effect of MPH alone is not large enough to equalize differences with controls in all HRQOL-domains.…”
Section: Discussionmentioning
confidence: 99%
“…It is striking that so few studies evaluated HRQOL and clinical outcome after medication for ADHD, including two stimulant (amphetamine) 10,11 and five nonstimulant (atomoxetine) studies [11][12][13][14][15] showing improvement in HRQOL psychosocial domains during treatment. As stimulants have emerged as the first-line effective therapy to treat ADHD, and as methylphenidate (MPH) has a positive effect both on behavioural ADHD symptoms and motor symptoms (handwriting), 16,17 medication with MPH seems to be the first choice in ADHD/DCD.…”
mentioning
confidence: 99%
“…Clinically significant effects are only seen after 4 to 6 weeks. It has been shown to be effective in a number of clinical trials [64,65]. The medication was well tolerated, with discontinuation rates due to adverse events of less than 5% in pediatric studies.…”
Section: Atomoxetinementioning
confidence: 98%